Sustainable Development In Sports Through Coaches Effective Guidelines For Planning A Plyometric Training Session - Nkiru Uzor , Theresa; Ujuagu, Nonye Ann; Uwa, Anthonia Chinyere (Athena: Physical Education and Sports Journal, 2024)
Plyometric is a form of advanced fitness training that uses fast muscular contractions to improve power and speed in the sports performance by coaches and athletes. The paper presents how plyometrics works, types of plyometric and benefits of using plyometrics are also offered. It highlighted a lot common mistakes coaches make while using plyometric training such as improper progression, skipping the prerequisites, not jumping enough, too much plyometrics, bad landing among others. The paper made some useful conclusions as well as recommendations that will improve athletics in modern sports such as NUGA and Olympic Games.